Exploratory social network analysis with Pajek - Nooy, Wouter de 1962-; Mrvar, Andrej ca. 20./21. Jh; Batagelj, Vladimir 1948- (Cambridge University Press, 2018)
An extensively revised and expanded third edition of the successful textbook on analysis and visualization of social networks integrating theory, applications, and professional software for performing network analysis (Pajek). The main structural concepts and their applications in social research are introduced with exercises. Pajek software and datasets are available, so readers can learn network analysis through application and case studies. In the end readers will have the knowledge, skills, and tools to apply social network analysis across different disciplines. A fundamental redesign of the menu structure and the capability to analyze much larger networks required a new edition. This edition presents several new operations including community detection, generalized main paths searches, new network indices, advanced visualization approaches, and instructions for installing Pajek under MacOSX. This third edition is up-to-date with Pajek version 5 and it introduces PajekXXL for very large networks and Pajek3XL for huge networks
Title from publisher's bibliographic system (viewed on 25 Jul 2018)
Keywords: Pajek (Electronic resource); Social networks / Mathematical models; Social networks / Computer simulation; Soziales Netzwerk; Netzwerkanalyse -- Soziologie; Pajek; Computersimulation; Mathematisches Modell